2013
DOI: 10.1038/pr.2013.180
|View full text |Cite
|
Sign up to set email alerts
|

Lectin pathway of complement activation and relation with clinical complications in critically ill children

Abstract: Background:Critically ill children are susceptible to nosocomial infections, which contribute to adverse outcomes. Deficiencies in the innate immunity lectin pathway of complement activation are implicated in a child's vulnerability to infections in conditions such as cancer, but the role during critical illness remains unclear. We hypothesized that low on-admission levels of the pathway proteins are, in part, genetically determined and associated with susceptibility to infectious complications and adverse out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 40 publications
3
21
0
1
Order By: Relevance
“…A low MASP-3 concentration upon PICU admission was independently associated with a higher risk of infection in this model (OR: 0.701 (95% CI: 0.562-0.864), P = 0.001). This confirmed the association we previously observed for MASP-3, with an even lower odds ratio than in the model without CL-L1 (OR: 0.809 (95% CI: 0.675-0.959), P = 0.02) (17). The independent associations of CL-L1 and MASP-3 with infection were maintained with the addition of the interaction between both Articles protein concentrations to the model, with a P value of 0.06 for the interaction variable ( Table 2).…”
Section: Association Of Cl-l1 Serum Concentrations Upon Picu Admissiosupporting
confidence: 80%
See 3 more Smart Citations
“…A low MASP-3 concentration upon PICU admission was independently associated with a higher risk of infection in this model (OR: 0.701 (95% CI: 0.562-0.864), P = 0.001). This confirmed the association we previously observed for MASP-3, with an even lower odds ratio than in the model without CL-L1 (OR: 0.809 (95% CI: 0.675-0.959), P = 0.02) (17). The independent associations of CL-L1 and MASP-3 with infection were maintained with the addition of the interaction between both Articles protein concentrations to the model, with a P value of 0.06 for the interaction variable ( Table 2).…”
Section: Association Of Cl-l1 Serum Concentrations Upon Picu Admissiosupporting
confidence: 80%
“…As for risk of infection, this association was in the opposite direction as that for MASP-3, showing a higher likelihood of earlier alive discharge at any time with a higher MASP-3 concentration (hazard ratio (HR) of 1.125 (95% CI: 1.046-1.205, P = 0.001). Again, this association was stronger than for the model without CL-L1 that was previously reported (HR: 1.088 (95% CI: 1.020-1.157), P = 0.01) (17). Addition of the interaction between both proteins had no major effect, with a P value of 0.92 for the interaction variable ( Table 3).…”
Section: Association Of Cl-l1 Serum Concentrations Upon Picu Admissiomentioning
confidence: 42%
See 2 more Smart Citations
“…However, other studies in adults have not found MBL to be associated with risk for sepsis (3942) or have reported a more nuanced picture that includes a mixture of both pro-inflammatory and anti-infection effects which may be beneficial or detrimental in varying disease states. (33, 34, 43) Specifically in pediatrics, six studies have demonstrated an association between lower MBL levels, or low-MBL producing haplotypes, and increased severity of infection-related disease (4, 5, 15, 16, 4446) while five studies showed similar findings to ours with a lack of association (12, 4650) and two studies concluded a possible protective role for low-producing MBL genotypes or levels. (12, 51)…”
Section: Discussionsupporting
confidence: 69%